Detection of a mosaic PIK3CA mutation in dental DNA from a child with megalencephaly capillary malformation syndrome. Issue 1 (January 2016) - McDermott, John H.; Byers, Helen; Clayton-Smith, Jill
Abstract : The megalencephaly capillary malformation syndrome (MCAP, OMIM 602501) is known to be associated with mosaic mutations in PIK3CA occurring during embryogenesis. Standard sequencing technologies are relatively poor at indentifying sequence changes that only affect a small percentage of cells, and the mutations are frequently not identified in lymphocyte DNA, with biopsies of the affected tissues often being required to detect mosaic mutations. Such invasive procedures are not always acceptable to parents. We describe the case of a patient in whom we were able to confirm a causative PIK3CA mutation, first found thorugh next-generation sequencing, in several tissue types including a secondary tooth. As part of this work, we were also able to begin validating dental tissue for potential use in genetic testing, as we achieved excellent DNA yields with minimal effort, even from deciduous teeth shed some years earlier.